Does AI Make Healthcare More Efficient? An Academic Perspective on Digital Transformation - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare systems is one of the most significant technological shifts of the 21st century. The central qu...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care